RANCANG BANGUN SISTEM INFORMASI E-LEARNING BERBASIS WEBSITE PADA SEKOLAH MENENGAH ATAS NEGERI 1 JONGGOL - Putri Nabila (2022)
State Senior High School 1 Jonggol (SMAN 1 Jonggol) is a public high school located in Bogor Regency, West Java. The learning process at SMA Negeri 1 Jonggol currently applies face-to-face and online by utilizing Google Classroom, zoom and similar digital platforms. The face-to-face learning process is carried out by meeting directly with the teacher concerned, as well as in the process of assigning assignments and collecting assignments are still carried out directly in the form of paper. SMA Negeri 1 Jonggol does not yet have an e-learning system that can provide convenience in the process of storing data and information that is used to assist the learning process both in providing teaching materials, assigning assignments, and collecting assignments. If the teacher in question is unable to attend, students are asked to do assignments or only read the material delivered through the picket teacher without direct control with the teacher concerned. Thus, it is necessary to have an e-learning system that can assist in teaching and learning activities. The method used in system development is the waterfall method which consists of several stages including: system requirements analysis, system design, program code generation, testing, and implementation. In this research, in analyzing the system requirements using the PIECES method and using the blackbox testing method to test the system built. The results of this study are a learning system in the form of website-based e-learning that can help schools in the teaching and learning process so that it becomes effective and efficient. And the system can be used as an information technology asset for the school.